Famine in Gaza, questions for research and preventive action - Vos, Rob; Elouafi, Ismahane; Swinnen, Johan (Springer, 2024)
The ongoing humanitarian crisis in Gaza is unprecedented in terms of the share of the population experiencing acute food insecurity and famine and the speed of the onset of the crisis. Research can help understand and anticipate the long-term impacts of the conflict on people and livelihoods, design more effective humanitarian support systems and identify options for creating resilient post-conflict livelihoods.